2021
DOI: 10.3390/ijms22052242
|View full text |Cite
|
Sign up to set email alerts
|

COMP and TSP-4: Functional Roles in Articular Cartilage and Relevance in Osteoarthritis

Abstract: Osteoarthritis (OA) is a slow-progressing joint disease, leading to the degradation and remodeling of the cartilage extracellular matrix (ECM). The usually quiescent chondrocytes become reactivated and accumulate in cell clusters, become hypertrophic, and intensively produce not only degrading enzymes, but also ECM proteins, like the cartilage oligomeric matrix protein (COMP) and thrombospondin-4 (TSP-4). To date, the functional roles of these newly synthesized proteins in articular cartilage are still elusive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 80 publications
0
40
0
Order By: Relevance
“…Such PK/CK scintigraphic ratio increase after surgery agrees with previously published results from our group in the meniscectomy and papain models of OA 16 , 25 . Hypertrophic changes in PG have been widely described in OA cartilage as a first line reparative reaction via an early increased synthesis of extracellular matrix (ECM) in damaged areas being followed at a later stage by degenerative destruction 26 – 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Such PK/CK scintigraphic ratio increase after surgery agrees with previously published results from our group in the meniscectomy and papain models of OA 16 , 25 . Hypertrophic changes in PG have been widely described in OA cartilage as a first line reparative reaction via an early increased synthesis of extracellular matrix (ECM) in damaged areas being followed at a later stage by degenerative destruction 26 – 31 .…”
Section: Discussionmentioning
confidence: 99%
“…29 COMP/TSP5 is also a well-established cartilage destruction marker in osteoarthritis. 58 Several reports have proposed that COMP/TSP5 is a promising diagnostic and prognostic marker, as well as disease severity. COMP/TSP5 has shown promise as a diagnostic and prognostic indicator and as a marker of the disease severity and the effect of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo , some scholars have revealed that Thbs4 is present in the articular cartilage but not in the growth plates of mice, which suggests low levels or even an absence of Thbs4 during the peak of articular cartilage development ( Jeschke et al, 2015 ). In vitro , Maly concluded that Thbs4 maintains porcine chondrocyte phenotype stability by promoting collagen and proteoglycan production ( Maly et al, 2021 ). Collagen IX has been shown to stabilize fibrous and proteoglycan networks, and Brachvogel’s study identified Thbs4 as a possible binding partner for collagen IX ( Brachvogel et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%